Evaluasi Manajemen Pengelolaan Obat pada Tahap Penyimpanan dan Penggunaan Obat di Apotek Rumah Sakit x - Syahrizal Ramadhani; Novie Herniyati; Depy Oktapian Akbar (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Availability of drugs when needed in sufficient quantities and guaranteed quality to support quality service in the hospital is the goal of drug management. Drug storage and use are important factors in drug management. if the management is not managed properly it will have a negative impact both medically, economically and socially. The purpose of the study was to evaluate the management of drug management at the stage of storage and use of drugs at the X Hospital Pharmacy compared to standard indicator values. This research was descriptive and evaluative with observation method used retrospective and concurrent data. The number of samples taken in this study were 100 prescriptions and 231 drug samples with proportional sampling technique. The data was analyzed using standard indicators that have been set by making a frequency and percentage table. The results of the study that did not meet the standards at the storage stage were dead stock of drugs (3,89%), expired/damaged drugs (2,17%), the match between physical drugs and stock cards (57,14%). At the drug use stage, the number of each drug item per prescription (2,62), the drug that can be delivered was 95,80%, and the percentage of drugs prescribed according to the formulary was 76,34%.